Effective Fixation of Carbon in g‐C3N4 Enabled by Mg‐Induced Selective Reconstruction. Issue 10 (16th February 2020) - Ding, Yiwang; Yu, Chang; Chang, Jiangwei; Yao, Chun; Yu, Jinhe; Guo, Wei; Qiu, Jieshan
Abstract: The methodology of metal‐involved preparation for carbon materials is favored by researchers and has attracted tremendous attention. Decoupling this process and the underlying mechanism in detail are highly required. Herein, the intrinsic mechanism of carbon fixation in graphitic carbon nitride (g‐C3 N4 ) via the magnesium‐involved carbonization process is reported and clarified. Magnesium can induce the displacement reaction with the small carbon nitride molecule generated by the pyrolysis of g‐C3 N4, thus efficiently fixing the carbon onto the in situ template of Mg3 N2 product to avoid the direct volatilization. As a result, the N‐doped carbon nanosheet frameworks with interconnected porous structure and suitable N content are constructed by reconstruction of carbon and nitrogen species, which exhibit a comparable photoelectric conversion efficiency (8.59%) and electrocatalytic performances to that of Pt (8.40%) for dye‐sensitized solar cells. Abstract : The mechanism of magnesium‐involved carbon fixation from g‐C3 N4 to metal‐free carbon materials is presented with the increased carbon yield. Such a reconstruction process is confirmed by gradually increasing characteristic peaks of sp 2 carbon and rearrangement of the CN chemical bond. The resultant N‐doped carbon nanosheet frameworks achieve a photoelectric conversion efficiency (8.59%) comparable to Pt for dye‐sensitized solar cells.